2018
DOI: 10.3390/cells7030023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carotid Smooth Muscle Cells during Phenotypic Transition

Abstract: Vascular smooth muscle cells (VSMCs) are central players in carotid atherosclerosis plaque development. Although the precise mechanisms involved in plaque destabilization are not completely understood, it is known that VSMC proliferation and migration participate in plaque stabilization. In this study, we analyzed expression patterns of genes involved in carotid atherosclerosis development (e.g., transcription factors of regulation of SMC genes) of VSMCs located inside or outside the plaque lesion that may giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…Furthermore, another study revealed that MKl2 functioned as a pro-migratory gene in VSMcs (34). in the present study, MKl2 was found to be underexpressed in the serum of patients with aS compared with that of healthy volunteers, which was consistent with the findings of a previous study (35). In addition, via gain-of-function and loss-of-function approaches, transfection with miR-142-5p inhibitor significantly increased the mRNA and protein expression level of MKL2 in HASMCs; however, transfection with MKl2-sirna resulted in a decreased MKL2 expression.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, another study revealed that MKl2 functioned as a pro-migratory gene in VSMcs (34). in the present study, MKl2 was found to be underexpressed in the serum of patients with aS compared with that of healthy volunteers, which was consistent with the findings of a previous study (35). In addition, via gain-of-function and loss-of-function approaches, transfection with miR-142-5p inhibitor significantly increased the mRNA and protein expression level of MKL2 in HASMCs; however, transfection with MKl2-sirna resulted in a decreased MKL2 expression.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports showing that DNA hypomethylating agents can remove the epigenetic “brake” and allow stem cells to undergo differentiation ( 17 ), we found that the DNA methylation inhibitor 5′-Aza not only upregulated expression of genes imperative for differentiation but also functionally depleted the LSC population and inhibited its colony formation ( 20 , 54 ). 5′-Aza-induced LSC differentiation was supported by the observation that 5′-Aza treatment significantly increased the expression of markers of fully differentiated smooth muscle cells, such as MYH11 ( 44 ). Notably, we found that RU486 pretreatment did not significantly affect the LM cells’ colony-forming activity and was less efficient in inhibiting LM regeneration compared with 5′-Aza treatment, suggesting that LSC deficient in steroid hormone receptors may remain quiescent, constituting a small population of cells resistant to RU486 treatment.…”
Section: Discussionmentioning
confidence: 88%
“…TIMP3, tissue inhibitor of metalloproteinase 3, regulates extracellular matrix at the tumor–stromal interface ( 39 ) and is critical in driving differentiation and decreasing tumorigenesis in the mammary gland and muscle tissues ( 40 , 41 ). The ROR2 pathway plays complex roles in stem cell function and carcinogenesis ( 42 , 43 ), and MYH11 is a marker of fully differentiated smooth muscle cells ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…These analyses, however, confirmed that the two genes were heterogeneously expressed throughout the vessel and lesion, with the majority of Cnn1 expressed in the wall as expected, as it is a VSMC marker and this is where most VSMC are located. 16 Cnn1-expressing cells were also found in the cap of the plaque, showing the involvement of VSMC in cap formation. 17 Timp2 was dispersed throughout the whole artery and both present in the wall and the plaque with a tendency towards a higher expression within the plaque itself ( Figure 6C-E).…”
Section: Liraglutide Treatment Effects On Gene Expressionmentioning
confidence: 90%